Molecular epidemiology of human Campylobacter jejuni shows association between seasonal and international patterns of disease. - McCarthy, N; Gillespie, I; Lawson, A; Richardson, J; Neal, K; Hawtin, P; Maiden, M; O'Brien, S (2012)
We sought to explain seasonality and other aspects of Campylobacter jejuni epidemiology by integrating population genetic and epidemiological analysis in a large 3-year longitudinal, two-centre, population-based study. Epidemiological information was collected for 1505 isolates, which were multilocus sequence-typed. Analyses compared pathogen population structure between areas, over time, and between clinical presentations. Pooled analysis was performed with published international datasets. Subtype association with virulence was not observed. UK sites had nearly identical C. jejuni populations. A clade formed by ST45 and ST283 clonal complexes showed a summer peak. This clade was common in a Finnish dataset but not in New Zealand and Australian collections, countries with less marked seasonality. The UK, New Zealand and Australian collections were otherwise similar. These findings map to known in-vitro differences of this clade. This identifies a target for studies to elucidate the drivers of the summer peak in human C. jejuni infection.